Ayah-Anak: Kajian Eksistensial dan Fenomenologis Atas Novel Bukan Pasarmalam, Karya Pramoedya Ananta Toer - Chai, Waty; Tonny; Lasmono, Hari K. (ANIMA Indonesian Psychological Journal, 2007)
Father-son relationship has been a common topic in quanti– as well qualitative research studies. While quantitative approach offers less analysis concerning the time continuum, qualitative approach tends to generalize the father concept. This research used the fenomenology perspective of Merleau-Ponty and existentialist perspectives of Sartre which are assumed to provide a diverse father concept. This approach was taken in accordance with the topic and purpose of this research, i.e. to add additional inventory towards the meaning of a father. The Bukan Pasarmalam novel (Toer, 2006) was the core of the analysis. Data were collected through critical and curious reading. Thoughts from the critical reading was the basis for analysis. Results reveal that (a) Bukan Pasarmalam is the auto- biography of its writer Pramoedya implicitly reflecting his personal needs, i.e. the desire to forgive his father; (b) the meaning of the father concept for “I” (as son) was understood as physical and spatial entity. Father and son relation was built upon a two-way perception, which are affecting each other and (c) the death of the father in a certain belief means a birth of a father for his child. Penelitian tentang relasi ayah-anak sering diangkat melalui pendekatan kuanti– maupun kualitatif. Pendekatan kuantitatif kurang menawarkan analisis dalam garis kontinum waktu, sedang- kan pendekatan kualitatif cenderung menyeragamkan konsep ayah. Penelitian ini menggunakan pen- dekatan fenomenologi Merleau-Ponty dan eksistensialisme Sartre yang dianggap mampu menawar- kan makna ayah dalam keberagaman. Pendekatan ini terkait erat dengan topik dan tujuan penelitian, yaitu sebagai inventarisasi tambahan tentang makna ayah. Bahan analisis adalah novel Bukan Pa- sarmalam (Toer, 2006). Data diperoleh melalui membaca kritis sambil selalu mempertanyakan isi novel tersebut. Pemikiran yang berasal dari membaca kritis akan menjadi dasar analisis. Hasil pene- litian menunjukkan (a) novel Bukan Pasarmalam merupakan karya otobiografis yang oleh penulisnya disampaikan dengan melibatkan kepentingan individualnya, yakni keinginan untuk memaafkan ayah- nya; (b) makna ayah bagi tokoh “aku” (sebagai anak) ternyata dimengerti dalam bentuk fisik dan kon- sep keruangan. Relasi ayah-anak terjalin dalam pencerapan dua arah dan saling memengaruhi; (c) ke- matian ayah dalam arti tertentu merupakan kelahiran seorang ayah bagi anak.